Biophysical evidence to support and extend the vitamin D‐folate hypothesis as a paradigm for the evolution of human skin pigmentation - Lucock, Mark D.; Jones, Patrice R.; Veysey, Martin; Thota, Rohith; Garg, Manohar; Furst, John; Martin, Charlotte; Yates, Zoe; Scarlett, Christopher J.; Jablonski, Nina G.; Chaplin, George; Beckett, Emma L. (American journal of human biology, 2022)
Objective To test the “vitamin D‐folate hypothesis for the evolution of human skin pigmentation.” Methods Total ozone mapping spectrometer (TOMS) satellite data were used to examine surface UV‐irradiance in a large (n = 649) Australian cross‐sectional study population. Genetic analysis was used to score vitamin D‐ and folate‐related gene polymorphisms (n = 22), along with two pigmentation gene variants (IRF4‐rs12203592/HERC2‐rs12913832). Red cell folate and vitamin D3 were measured by immunoassay and HPLC, respectively. Results Ultraviolet radiation (UVR) and pigmentation genes interact to modify blood vitamin levels; Light skin IRF4‐TT genotype has greatest folate loss while light skin HERC2‐GG genotype has greatest vitamin D3 synthesis (reflected in both TOMS and seasonal data). UV‐wavelength exhibits a dose–response relationship in folate loss within light skin IRF4‐TT genotype (305 > 310 > 324 > 380 nm). Significant vitamin D3 photosynthesis only occurs within light skin HERC2‐GG genotype, and is maximal at 305 nm. Three dietary antioxidants (vitamins C, E, and β‐carotene) interact with UVR and pigmentation genes preventing oxidative loss of labile reduced folate vitamers, with greatest benefit in light skin IRF4‐TT subjects. The putative photosensitiser, riboflavin, did not sensitize red cell folate to UVR and actually afforded protection. Four genes (5xSNPs) influenced blood vitamin levels when stratified by pigmentation genotype; MTHFR‐rs1801133/rs1801131, TS‐rs34489327, CYP24A‐rs17216707, and VDR‐ApaI‐rs7975232. Lightest IRF4‐TT/darkest HERC2‐AA genotype combination (greatest folate loss/lowest vitamin D3 synthesis) has 0% occurrence. The opposing, commonest (39%) compound genotype (darkest IRF4‐CC/lightest HERC2‐GG) permits least folate loss and greatest synthesis of vitamin D3. Conclusion New biophysical evidence supports the vitamin D‐folate hypothesis for evolution of skin pigmentation.